Web Based Application for Early Detection of Vitamin and Mineral Deficiency - Sevani, Nina; Chandra, Yosua Jaya (CommIT (Communication and Information Technology) Journal, 2016)
Deficiency of vitamin and mineral as part of micronutrient deficiency may lower human productivity. In general, lack of public understanding about micronutrient, limited number of nutritionist, time and cost, became the reason for people reluctant to meet nutritionist. The use of web-based computer application can be implemented to overcome the difficulty to get nutritionist’s services. Using the application, user can detect and check their micronutrient condition independently. User can submit their physical condition by answering questions from the application. Using forward chaining inference, data from user will be proceed using certainty factor method. The application’s output are the possible type of micronutrient’s deficiency and the weight that shown the level of confidence of the result. The evaluation process shown that the application functioning properly in line with the expectation. Beside helping people to make early detection independenly, the presence of the application is also expected to increase public awareness about the importance of micronutrient in their life.